2003
DOI: 10.1164/rccm.200211-1292oc
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Dysfunction in Transfusion-dependent Patients with Thalassemia Major

Abstract: Pulmonary function tests were performed on 62 transfusion-dependent patients with thalassemia major, ranging in age from 8 to 33 years, and receiving chelation therapy with desferrioxamine or deferiprone. Percent predicted values for FVC, FEV1, and PEF were significantly reduced, whereas FEV1/FVC and maximal expiratory flow at 25% FVC were within normal limits, indicating a restrictive disease. Both FVC and FEV1 were negatively correlated with transfusional iron burden as indexed by age. Single-breath carbon m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
48
1
17

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 22 publications
9
48
1
17
Order By: Relevance
“…Among the thalassemic subjects, restrictive lung function abnormality was the most common (42/63) observation documented in this study. Our findings are consistent with those of Carnelli et al, 1 Factor et al, 2 Tai et al, 5 Luyt et al, 6 and Filosa et al 7 What is unique to our study is that it was performed exclusively in children, while those studies mentioned earlier were all performed in both children and adults, with a considerably older mean age. Therefore, our study shows that lung dysfunction in thalassemic patients has occurred since childhood.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Among the thalassemic subjects, restrictive lung function abnormality was the most common (42/63) observation documented in this study. Our findings are consistent with those of Carnelli et al, 1 Factor et al, 2 Tai et al, 5 Luyt et al, 6 and Filosa et al 7 What is unique to our study is that it was performed exclusively in children, while those studies mentioned earlier were all performed in both children and adults, with a considerably older mean age. Therefore, our study shows that lung dysfunction in thalassemic patients has occurred since childhood.…”
Section: Discussionsupporting
confidence: 93%
“…However, no correlation was found between serum ferritin levels and any of the lung function values. This finding supported those discovered by Tai et al, 5 and Luyt et al 6 , but contrasted with studies by Carnelli et al, 1 Factor et al, 2 and Filosa et al 7 It is suggested that the duration of iron overload may be more important than the actual amount of iron provided through transfusions. 2 Moreover, serum ferritin levels change during the process of chelation, and do not necessarily reflect total body iron stores.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Hastaların %55'inin SFT'si normal olarak bulunurken geriye kalan %34'ünde ise difüzyon bozukluğu saptanmıştır 80 . Birçok çalışmada da β -TM tanılı hastalarda temel solunum sistemi bozukluğunun obstrüktif veya restriktif değil difüzyon bozukluğu olduğu öne sürülmüştür 72,80,87 . Bu durumun düşük hemoglobin konsantrasyonunun yanı sıra, ilerleyen zamanlarda alveoler-kapiller membran kalınlığının artışı ile difüzyon kapasitesinde azalma neticesinde görüldüğünü öne sürmüşlerdir.…”
Section: Solunum Sistemi Bulgularıunclassified